Damage to formation surrounding flooding wells: modelling of suspension filtration with account of particle trapping and mobilization; Journal of Physics: Conference Series; Vol. 925 : Joint 12th International Conference: "Two-Phase Systems for Space and Ground Applications" and 2nd International School of Young Scientists "Interfacial Phenomena and Heat Transfer" - Boronin S. A. Sergei; Tolmacheva K. I.; Osiptsov A. A. Andrei; Sitnikov A. N. Alexander; Yakovlev A. A. Andrey Alexandrovich; Belozerov B. V. Boris Vladimirovich; Belonogov E. V. Evgenii; Galeev R. R. Rail (2017, 2017)
Title screen